Pengaruh Motivasi Kerja Guru terhadap Hasil Belajar Mengajar SMA Semen Padang - Husna, Nikmatul (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine and analyze the influence of teacher work motivation on teaching and learning outcomes at SMA Semen Padang. The population of this study were all teachers and employees at SMA Semen Padang. A sample of 35 respondents was taken using a purposive sampling technique, namely determining the sample by taking a sample or data source with certain considerations, for example the person is considered to know what we expect best, or he is the ruler making it easier for researchers. to obtain the required information. Researchers used a questionnaire as a tool to collect data. Based on the hypothesis in this study, it is suspected that teacher work motivation has a positive and significant effect on teaching and learning outcomes at Semen Padang High School. The data analysis method that the authors used in this study were validity test, reliability test, variable descriptive analysis test, simple linear regression analysis, t test and F test) on teaching and learning outcomes, this is evidenced by the probability value of the significance of teacher work motivation of 0.000 which smaller than 0.05. From the F test it can be concluded that the regression model can be used to predict teacher work motivation which has a positive and significant effect on teaching and learning outcomes with a significant probability value generated of 0.000 which is smaller than 0.05.